The effective connectivity of the default mode network following moderate traumatic brain injury - Rahman, M. R. Abdul; Abd Hamid, A. I.; Noh, N. A.; Idris, Z.; Abdullah, J. M. (Iop Publishing Ltd, 2024)
Indexed by WOS/SCOPUS